Cultivo de Chlorella vulgaris em vinhaça convencional e biodigerida tratadas : uma abordagem ecofisiológica - Candido, Camila (Universidade Federal de São Carlos, 2015)
Vinasse is a waste of sugarcane industry and, due to the presence of organic matter and mineral nutrients, it has been used for the irrigation of the sugarcane crops. However, its composition limits such application due to soil salinization. The anaerobic fermentation of vinasse generates biogas that is used as energy source in the sugarcane industry itself. The fermented vinasse results in biodigested vinasse. The development of techniques for residue use can contribute to cleaner production systems. In this research, we evaluated treated conventional and biodigested vinasses for the growth of Chlorella vulgaris. The treatment consisted of filtering the vinasses through smectite clay and activated carbon, or centrifugation. Concentrations of 10, 20, 30, 40, 50, 60, 70, 80, 90 and 100% of treated vinasses were tested. Cell density, absorbance at 570 nm, pH and electrolyte conductivity were quantified daily in a six day experiment. Based in cell density, specific growth rates were calculated. Growth rates higher than the controls were obtained in 60% conventional filtered vinasse and 10% conventional centrifuged one, as well as in 80% biodigested filtered vinasse and 20% biodigested centrifuged vinasse. In general, the filtered vinasse was superior in relation to the centrifuged one regarding higher residue concentration that supported microalgae growth. After microalgae acclimation we evaluated the photosynthetic performance of C. vulgaris in the best vinasses conditions and the biochemical composition of the biomass present in the vinasse, which besides the microalgae contained other microorganisms, such as bacteria and fungi, since it was not sterilized. Specific growth rate for C. vulgaris in 60% filtered conventional vinasse was 1.6 d-1 and 1.5 d-1 in the 80% filtered biodigested vinasse, representing increases of up to 84 x in cell density compared to the initial. In the LC Oligo control the growth rate was ~ 0.9 d-1 and in the BG11 it was 1,1 d-1. Although the better C. vulgaris growth in the treated vinasses, photosynthetic efficiency and its related parameters were better in the control than in the vinasses. These results together with those of chlorophyll a concentration suggest that the microalgae have possibly used a mixotrophic metabolism while in the vinasses. We observed higher biomass accumulation in the vinasses than in the controls. A reduction of total dissolved organic carbon and dissolved mineral elements up to 50%, as well as bacteria and fungi, were detected in the vinasse after microalgae growth. This study is a contribution to the knowledge of microalgae physiology in a residue and to the development of cleaner ethanol production system.
Keywords: Microalga; Filtragem; Fotossíntese; Resíduos; Microalgae culture; Filtering; Photosynthesis; Residue; CIENCIAS BIOLOGICAS::ECOLOGIA